2016
DOI: 10.1152/jn.00215.2016
|View full text |Cite
|
Sign up to set email alerts
|

Pain anticipatory phenomena in patients with central poststroke pain: a magnetoencephalography study

Abstract: Gopalakrishnan R, Burgess RC, Lempka SF, Gale JT, Floden DP, Machado AG. Pain anticipatory phenomena in patients with central poststroke pain: a magnetoencephalography study. J Neurophysiol 116: 1387-1395, 2016. First published June 29, 2016 doi:10.1152/jn.00215.2016.-Central poststroke pain (CPSP) is characterized by hemianesthesia associated with unrelenting chronic pain. The final pain experience stems from interactions between sensory, affective, and cognitive components of chronic pain. Hence, managing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 64 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…34 Because pain anticipation is highly linked to pain chronification phenomena and to pain-related limited use of the affected extremities (and therefore linked to disability), we also believe that clinically effective VS/ALIC DBS will likely be associated with partial normalization of the neurophysiological correlates of pain anticipation. 35 In conclusion, VS/ALIC DBS was safe and effective in addressing the affective component of pain in patients with PSPS but not in reducing disability. We demonstrated that active versus sham VS/ALIC DBS produced significant improvements in multiple outcome measures related to the affective sphere of chronic pain.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…34 Because pain anticipation is highly linked to pain chronification phenomena and to pain-related limited use of the affected extremities (and therefore linked to disability), we also believe that clinically effective VS/ALIC DBS will likely be associated with partial normalization of the neurophysiological correlates of pain anticipation. 35 In conclusion, VS/ALIC DBS was safe and effective in addressing the affective component of pain in patients with PSPS but not in reducing disability. We demonstrated that active versus sham VS/ALIC DBS produced significant improvements in multiple outcome measures related to the affective sphere of chronic pain.…”
Section: Discussionmentioning
confidence: 82%
“…We hypothesize that clinically effective DBS will be associated with significant changes in the pain neuromatrix . Because pain anticipation is highly linked to pain chronification phenomena and to pain‐related limited use of the affected extremities (and therefore linked to disability), we also believe that clinically effective VS/ALIC DBS will likely be associated with partial normalization of the neurophysiological correlates of pain anticipation …”
Section: Discussionmentioning
confidence: 99%
“…To investigate the neural substrates of pain affect and its modulation by DBS of the ventral striatum, we previously studied the same patient cohort using an event‐related magnetoencephalography (MEG) paradigm (18‐20). Our findings were twofold.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with DRS no longer experience heightened anxiety from the anticipation of pain at the affected location compared to the unaffected side, possibly indicating neuronal habituation to painful stimuli [19]. In this instance, the patient already experiences unrelenting pain, and thus the threat of further stimuli loses salience [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this instance, the patient already experiences unrelenting pain, and thus the threat of further stimuli loses salience [19]. Larger neuronal losses after an infarct, in combination with proliferation of glia or microglia in the perilesional area, can lead to more severe allodynia [20].…”
Section: Introductionmentioning
confidence: 99%